2015
DOI: 10.3109/09638237.2015.1019044
|View full text |Cite
|
Sign up to set email alerts
|

“Work is good for me”: views of mental health service users seeking work during the UK recession, a qualitative analysis

Abstract: Despite economic recession, an IPS service was implemented and regarded as satisfactory to service users seeking work. Although many found obtaining employment difficult, they would still advise others that work is worthwhile, suggesting that the context of recession has not discouraged them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…Two mixed-methods studies were excluded because it was not possible to differentiate data obtained with qualitative and quantitative methods [ 41 , 42 ]; a third study was excluded because we could not clearly identify the views reported by PwCDs [ 43 ]. This led to a total of 24 publications included in our review [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The flow chart of the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two mixed-methods studies were excluded because it was not possible to differentiate data obtained with qualitative and quantitative methods [ 41 , 42 ]; a third study was excluded because we could not clearly identify the views reported by PwCDs [ 43 ]. This led to a total of 24 publications included in our review [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The flow chart of the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the included qualitative studies were most often persons suffering from mental disorders [ 44 , 45 , 46 , 48 , 50 , 52 , 56 , 59 , 60 , 61 , 62 , 63 , 67 ]. Three studies included persons with musculoskeletal disorders [ 47 , 51 , 55 ], two studies persons with cancer [ 49 , 66 ], two studies persons with mental and musculoskeletal disorders [ 53 , 64 ], and two studies a broad mix of persons with long-term conditions [ 54 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25,26 Although research with people with severe mental disorders suggests they want to work, the barriers are substantial and include symptoms of the mental condition, effects of treatment, a poor sickness record and lack of confidence. 27,28 There is a complex trade-off between providing security and dignity for people who are mentally incapacitated and unable to work, and creating a 'disability trap' that produces a culture of dependence and demoralisation. 29 It is a particular concern that individuals with mental disorders show an increasing tendency to be claiming sickness and long-term disability benefits, since it has been shown that such people are unlikely ever to rejoin the workforce.…”
Section: Consequences Of Worklessnessmentioning
confidence: 99%